How Far the Authorities are Going to go on Tackling Political Motive Hoax Spreading - Samudra, Anton Hendrik (Kertha Patrika, 2021)
This paper identifies hoax as a cyberspace social problem which can have a negative impact toward public order, both in cyberspace and real life. It also elaborates how a hoax is different from fake news for its characteristic. A hoax could cause horizontal conflict, especially in Indonesia when it is about the most recent common political commodities, which are race, ethnicity, religion, intergroup (SARA). Every government has interest on maintaining public order to keep the sustainability of society. Criminal law is designed to be the ultimate tool of social engineering through deterrence effect. The problem is how far the law enforcement is going to go to eradicate the hoax spreading, because the issues of freedom of speech/information.The research is conducted by using a conceptual approach in a normative legal study. Secondary data also provided in this paper to grasp the factual problems as the threat that needed to be encountered. The first part of the paper elaborates the freedom of speech/information, cyberspace, and social media. The second part is explanation of profile of hoax in Indonesia. The third part is elaboration of criminal statutes of hoax distribution using information communication technology. The last part is on how far the government and law enforcement synergize and how far they going to go in handling hoaxes and the sources to prevent and contain further damage. The findings are the blocking and taking down is not just about depraving internet user’s rights, but balancing between the freedom and public order. In order to be justifiable and balanced, the government needs to consider objectively whether the content was a threat that disrupting public order (moreover, national security), while the law enforcement could confiscate the electronic system involved and it should have been through appropriate criminal procedure.